2016
DOI: 10.1128/jvi.02449-15
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Sapelovirus Uses α2,3-Linked Sialic Acid on GD1a Ganglioside as a Receptor

Abstract: The receptor(s) for porcine sapelovirus (PSV), which causes diarrhea, pneumonia, polioencephalomyelitis, and reproductive disorders in pigs, remains largely unknown. Given the precedent for other picornaviruses which use terminal sialic acids (SAs) as receptors, we examined the role of SAs in PSV binding and infection. Using a variety of approaches, including treating cells with a carbohydrate-destroying chemical (NaIO4), mono- or oligosaccharides (N-acetylneuraminic acid, galactose, and 6′-sialyllactose), lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…Our previous results have demonstrated that SV-A could recognize α2,3-linked SA as a receptor (Kim et al , 2016), suggesting that SV-A might be able to infect and induce pathology in both pigs and chicks. To determine whether SV-A could induce diarrhoea and faecal viral shedding in piglets and chicks, 3-day-old piglets obtained from sows by hysterectomy and 3-day-old specific pathogen-free (SPF) chicks were orally inoculated with 2×10 9 or 5×10 8 p.f.u.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous results have demonstrated that SV-A could recognize α2,3-linked SA as a receptor (Kim et al , 2016), suggesting that SV-A might be able to infect and induce pathology in both pigs and chicks. To determine whether SV-A could induce diarrhoea and faecal viral shedding in piglets and chicks, 3-day-old piglets obtained from sows by hysterectomy and 3-day-old specific pathogen-free (SPF) chicks were orally inoculated with 2×10 9 or 5×10 8 p.f.u.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that SV-A could utilize α2,3-linked SA on GD1a glycolipid as a receptor (Kim et al , 2016). Indeed, glycolipid-associated α2,3-terminal SA is abundant on the cell surface of both avian and porcine species (de Graaf & Fouchier, 2014; Raman et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations